2018
DOI: 10.1038/s41598-018-30832-9
|View full text |Cite
|
Sign up to set email alerts
|

Preattentive and Predictive Processing of Visual Motion

Abstract: Interaction with the environment requires fast and reliable sensory processing. The visual system is confronted with a continuous flow of high-dimensional input (e.g. orientation, color, motion). From a theoretical point of view, it would be advantageous if critical information was processed independent of attentional load, i.e. preattentively. Here, we hypothesized that visual motion is such a critical signal and aimed for a neural signature of its preattentive encoding. Furthermore, we were interested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
2
14
1
Order By: Relevance
“…In preattentive vision, a large range of the human visual field is inspected in parallel without requiring a change in focal attention [38,39]. Although information processing capability is limited in preattentive visual processing, basic information along dimensions of texture, colour and motion can be handled in parallel and responded to rapidly [3840]. Visual processing that requires focal attention over the limited range of the fovea occurs more slowly.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In preattentive vision, a large range of the human visual field is inspected in parallel without requiring a change in focal attention [38,39]. Although information processing capability is limited in preattentive visual processing, basic information along dimensions of texture, colour and motion can be handled in parallel and responded to rapidly [3840]. Visual processing that requires focal attention over the limited range of the fovea occurs more slowly.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…This integration may occur at relatively high hierarchical stages of neural processing, before the information is relayed to the pursuit and saccadic components of the oculomotor system. Among the cortical areas involved in oculomotor control, frontal and supplementary eye fields could represent reasonable candidates, since their neural activity has been related to the extrapolation of occluded target motion in conjunction with other brain areas, such as the lateral intraparietal cortex and the cerebellum (Assad & Maunsell, 1995;Eskandar & Assad, 1999;Fukushima, Yamanobe, Shinmei, & Fukushima, 2002;Barborica & Ferrera, 2003Olson, Gatenby, Leung, Skudlarski, & Gore, 2004;Nagel et al, 2006;Xiao, Barborica, & Ferrera, 2007;Fukushima et al, 2008;O'Reilly, Mesulam, & Nobre, 2008;Cerminara, Apps, & Marple-Horvat, 2009;Ferrera & Barborica, 2010;Schmitt, Klingenhoefer, & Bremmer, 2018). Moreover, because of their responsiveness to vestibular stimulation, frontal and supplementary eye fields have been associated with the vestibular network, a constellation of cortical and subcortical brain areas receiving vestibular input that neuroimaging and transcranial magnetic stimulation studies have indicated as putative neural correlates of the internal model of gravity (Guldin & Grüsser, 1998;Brandt & Dieterich, 1999;Indovina et al, 2005;Bosco et al, 2008;Miller et al, 2008;Delle Monache et al, 2017; for reviews, see Dieterich & Brandt, 2015).…”
Section: Both Saccadic and Smooth-pursuit Control Use Internalized Grmentioning
confidence: 99%
“…Perceptual continuity is a mental construct of the brain [146][147][148], even if eyes follow an object by smooth pursuit [149]. Perceptual illusion [150] occurs if the head moves, then heading is compressed [151][152][153]. The mature brain endows perspective upon space, with the role of foreshortening cues [154,155].…”
Section: Blinks and Saccades Induce Perception Errorsmentioning
confidence: 99%